2003
DOI: 10.4049/jimmunol.171.12.6519
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Repellent Slit2 Inhibits Dendritic Cell Migration and the Development of Immune Responses

Abstract: One of the essential functions of dendritic cells is to take up Ags in peripheral tissues and migrate into secondary lymphoid organs to present Ags to lymphocytes for the induction of immune responses. Although many studies have demonstrated that the migration of dendritic cells is closely associated with the development of immune responses, little is known about factors that inhibit dendritic cell migration and control the extent of immune responses to Ag stimulation. We show that Slit2, a neuronal repellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 50 publications
4
83
0
1
Order By: Relevance
“…Two examples are slit2 and Sema3A that in addition to their role in angiogenesis and neuronal development are very potent inhibitors of dendritic cell activation and of the immune response. 167,168 However, it is not because tumor cells express some axon guidance proteins that their function in these cells is identical and it would probably be a mistake to directly apply models based on neurons to tumor cell biology. For instance, the semaphorin receptors appear to be distinct in the immune system and nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Two examples are slit2 and Sema3A that in addition to their role in angiogenesis and neuronal development are very potent inhibitors of dendritic cell activation and of the immune response. 167,168 However, it is not because tumor cells express some axon guidance proteins that their function in these cells is identical and it would probably be a mistake to directly apply models based on neurons to tumor cell biology. For instance, the semaphorin receptors appear to be distinct in the immune system and nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The SLIT molecules (SLIT1, SLIT2 and SLIT3) bind with members of the roundabout, axon guidance receptor (ROBO) family of receptors and interact with heparan sulphate chains [16]. In retinal axons in vivo, SDF-1 has been shown to modulate SLIT and ROBO signalling [17], while in leucocytes SLIT2 may modulate SDF-1-mediated chemotaxis [14,18,19], transendothelial migration and adhesion of T cells [13], and migration of dendritic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the SLIT protein family are large glycoproteins that are important for nervous system development, but can be expressed by epithelial [14] and endothelial cells [15]. The SLIT molecules (SLIT1, SLIT2 and SLIT3) bind with members of the roundabout, axon guidance receptor (ROBO) family of receptors and interact with heparan sulphate chains [16].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The interaction of Slits with Robo has a significant effect on axon guidance and neuronal migration. [13][14][15] …”
mentioning
confidence: 99%
“…[9][10][11][12] The interaction of Slits with Robo has a significant effect on axon guidance and neuronal migration. [13][14][15] Recently, Slit2 has been reported to play a significant role in carcinogenesis. Some studies have indicated that in human cancers, the Slit2 gene is frequently inactivated by hypermethylation in the promoter region or by allele loss in lung, breast, ovarian, 16 and colorectal cancers as well as malignant gliomas, [17][18][19] suggesting a tumor-suppressive role for Slit2.…”
mentioning
confidence: 99%